Assessing the Impact of EDTA Chelating Effect on some Macro- and Microminerals in Prussian Carp (Carassius Gibelio) Tissues - Marioara Nicula; Iosif Gergen; Monica Harmanescu; Ionuț Banatean-Dunea; Adela Marcu; Eliza Simiz; Tiberiu Polen; Mihai Lunca (Scientific Papers Animal Science and Biotechnologies, 2023)
Chelators are used in chemical analysis, in medical aplications, as water softeners, as decontamination agents on radioactive surfaces and they are ingredients in many commercial products such as shampoos and food preservatives. Such a synthetic chelator is EDTA (ethylenediaminetetraacetic acid). It is considered one of the tools that promises to control the heavy metal pollution in aquaculture. EDTA attaches itself to heavy metals and carries the metals from the fish body. EDTA can also slow free-radical activity produced by heavy metals in the body. Because its ability to sequester metal ions, we tried to estimate the potential risks of a chronic exposure to EDTA on tissue mobilization of some metals which have an essential role in realization of different cell functions in Prussian carp specimens. Ca, Mg, Fe, Zn. Mn and Cu, were the mineral elements we have targeted in this study.  It was found that these minerals have a trend of their tissues distribution and concentration in the body of the control specimens (higher or lower related to other similar works) and EDTA presence in water led to a significant decreasing of their level in all tissues analyzed in a dose-dependent manner.